International finance for dummies - Evrensel, Ayse Y. (John Wiley & Sons, 2013)
Get the most out of your international finance course! This guide covers need-to-know information for understanding the foundations of international finance, factors that affect and influence exchange rates, and how real-time connectedness impacts the global economy.